Stress Hyperglycemia as Predictive Factor of Recurrence in Children with Febrile Seizures - Raluca Maria Costea; Ionela Maniu; Luminita Dobrota; Bogdan Neamtu (Brain Sciences, 2020)
Stress hyperglycemia and hyperlactatemia are commonly referred to as markers of stress severity and poor outcome in children with severe acute illness or febrile seizures. Our prospective study aimed to explore the risk factors for stress hyperglycemia and the predictive value of stress hyperglycemia for febrile seizure recurrence. We evaluated as risk factors for blood glucose level, serum lactate, acid−base status, and the clinical parameters relevant to the severity of the infectious context or to febrile seizure event: fever degree, fever duration, seizure type and aspect, seizure duration, and recurrence. Among 166 febrile seizures events in 128 children, the prevalence of stress hyperglycemia (blood glucose >140 mg/dl) was 16.9%. The comparison of the stress versus non-stress hyperglycemia groups revealed lower pH (median (interquartile range): 7.46 (7.37, 7.53) vs. 7.48 (7.42, 7.53), p = 0.049), higher lactate levels (30.50 mg/dl (15, 36) vs. 19.50 mg/dl (15, 27), p = 0.000), slightly lower HCO3 (20.15 (20.20, 21.45) vs. 21.35 (20, 22.40), p = 0.020) in the stress hyperglycemia group. Multiple logistic regression analysis showed that prolonged febrile seizures (>15 min), recurrent febrile seizure (>1 seizure), focal seizure type, body temperature ≥39.5 °C and higher lactate values were significantly associated with stress hyperglycemia. These findings suggest a particular acute stress reaction in febrile seizures, with stress hyperglycemia playing an important role, particularly in patients with a recurrent seizure pattern. A more complex future approach linking pathogenic mechanisms and genetic traits would be advised and could provide further clues regarding recurrence pattern and individualized treatment.